3D printing of multifunctional materials for sensing and actuation: Merging piezoelectricity with shape memory. (5th June 2020) - Bodkhe, Sampada; Ermanni, Paolo
Graphical abstract: Highlights: A single hybrid material that acts both as a sensor and an actuator. Shape memory behavior of polymer blends exploited for actuation. Piezoelectric properties of barium titanate nanoparticles utilized for sensing. Abstract: Multifunctional materials play a vital role in attaining adaptability, autonomy and many such benefits with no added material cost and weight. However, even today multifunctional structures entail more than one material to obtain combined sensing and actuation, resulting in incompatibility during fabrication as well as service. In this study, a single material that changes its shape with temperature and simultaneously measures the extent of this deformation is designed, making it a viable solution to remotely monitor actuators or change the orientations of sensors, for example in pipelines, space, or the human body. To realize this combination of properties, a composite made from shape-memory polymers – PLA and PEA, and piezoelectric barium titanate nanoparticles is developed and investigated. We explore the possibilities to tune our actuation temperatures from 100 °C down to body temperatures, and present a robust sensor capable of withstanding temperatures ranging from 23 °C to 100 °C, and to over 5000 operation cycles. We use direct-write 3D printing to form different shapes from this multifunctional material. This shape-memory composite has a recovery rate of ∼98% and the sensor has a linear response in the force range of 0.1 – 1 N. Our material with presented improvements towards 4D printing offers applications in electroactive scaffolds, artificial organs for surgical training as well as adaptive electronics.